ANALISIS PERENCANAAN BAHAN BAKU TRIPLEK DAN PENERAPAN ENTERPRISE RESOURCE PLANNING (ERP) DI INDUSTRI FURNITURE - Dian Fahma Suryani; Hery Murnawan (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Enterprise Resource Planning (ERP). Enterprise Resource Planning (ERP) is a sophisticated database system. Manufacturing companies have a production process, the production process is a process where raw materials are converted into finished products or have added value. Before carrying out the production process, it is necessary to determine raw material planning using the Material Requirement Planning (MRP) method. Material Requirement Planning (MRP) is a method required for production planning or procurement of components to meet the master production schedule (JIP). In the production process, especially in the procurement of raw materials, there are problems, namely the process of calculating the number of raw materials is only done by estimating the amount of production in advance and there is no calculation using this method and there is no ability within the company to control inventory so that the determination of the materials that will be needed is irregular. Therefore, researchers will determine the planning of raw material requirements for a certain period using the Material Requirement Planning (MRP) method. Then integration with the company's ERP system is one way to solve the problem so that it can help companies improve business process performance. Implementation of ERP applications in business processes is expected to improve business performance such as reducing excessively high lead times, improving customer service performance, eliminating required stages and others